Opłacalność zastosowania pomp cieplnych do celów grzewczych w porównaniu z metodami tradycyjnymi - Małecki, Piotr P. (Profitability of Using Heat Pumps for Heating Purposes in Comparison with Traditional Methods, 2009)
The paper shows the attempt to assess the effectiveness of heat pump usage in a family house (area of 150-200 m2). The heat pump utilizes heat included in air and is one of the methods of sustainable energy utilization. There is relative assessment made by comparing heat pump in regard to cost effectiveness with another typical way of energy production - a gas fired boiler. The calculations that are made, covering also ecological costs, show that the heat system based on heat pump is more cost effective than the gas fired boiler only in case the gas grid is not close to a house. Cost effectiveness ratio, showing the cost of getting usable effect in form of energy unit production, in case of heating installation based on heat pump, equaled 0.4098 PLN/kilowatt-hour. At the same time the ratio for installation based on gas fired boiler amounted to 0.4038 PLN/kilowatt-hour in case of short distance of gas grid from a house (10-15 m) up to 0.4447 PLN/kilowatt-hour if the distance rose to 150-200 m.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 111-120